The Effect of Forgiveness on Happiness in Adolescents after Broken Love in Palembang City - Susanto, Mawar Rias; Darmayanti, Kusumasari Kartika Hima (Jurnal Sains Psikologi, 2023)
Adolescents who have ended their romantic relationship experience negative emotions such as sadness and charging. However, this must be followed up so they can focus on happiness. Therefore, this study aimed to determine how the effect of forgiveness on the happiness of adolescents after broken love in Palembang City. This study used a quantitative research design with non-experimental. The sampling technique was purposive sampling (n equals 360) in Palembang City. The research instrument uses The Heartland Forgiveness Scale and The Oxford Happiness Questionnaire. The research procedure uses two methods, namely Google Forms and paper. The data analysis method used in this study was a simple linear regression technique assisted by using IBM SPSS 26 for Windows. The results of this study indicate that forgiveness has a significantly positive effect on happiness in broken-up adolescents by 0.05, which means that adolescents who have high forgiveness have a good effect on happiness. These findings enable further research to offer interventions for forgiveness to increase happiness in adolescents after a breakup.